Specifics of the Taxation of Transfer of Shares in Companies Owning Immovable Properties Based on the VAT Act - Ranchev, Georgi (Research Papers, 2020)
The intensity of the tax control regarding the compliance with the VAT legislation has a direct impact on the amount of revenues from VAT in the state budget. In recent years the practice of the National Revenue Agency related to VAT treatment of the transfer of shares in companies owning immovable properties is rather ambiguous. Based on recent Supreme Administrative Court and ECJ decisions upcoming changes in the legislation could be expected.